2022
DOI: 10.1200/jco.2022.40.28_suppl.221
|View full text |Cite
|
Sign up to set email alerts
|

PROACT: Implementing a PROACTive care pathway to empower and support breast cancer (BC) survivors.

Abstract: 221 Background: Optimal comprehensive survivorship care, beyond screening of recurrences and new cancers, and including health promotion, management of physical as well as psychosocial needs and chronic conditions is insufficiently delivered. To increase patient (pt) empowerment and maximize the uptake of multidisciplinary strategies serving all survivorship needs, we implemented a proactive survivorship care pathway offered for pts with early BC at the end of their primary treatment phase (surgery, chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 53 Promoting periodic institutional educational activities with practical case discussions, identification of engaged health care professionals, development of symptom-management decision aids, and referral processes may help initiate this multidisciplinary dynamic. 54 (iii) Addressing modifiable risk factors for sexual concerns as appropriate, including the screening and management of emotional distress and weight balance, 55 and supporting patients with nonmodifiable risk factors such as the use of adjuvant therapies by offering them strategies to mitigate its treatment-related side-effects. (iv) Assess and reassess sexual health across the whole cancer care continuum at varied points of the patient journey to address any changes.…”
Section: Discussionmentioning
confidence: 99%
“… 53 Promoting periodic institutional educational activities with practical case discussions, identification of engaged health care professionals, development of symptom-management decision aids, and referral processes may help initiate this multidisciplinary dynamic. 54 (iii) Addressing modifiable risk factors for sexual concerns as appropriate, including the screening and management of emotional distress and weight balance, 55 and supporting patients with nonmodifiable risk factors such as the use of adjuvant therapies by offering them strategies to mitigate its treatment-related side-effects. (iv) Assess and reassess sexual health across the whole cancer care continuum at varied points of the patient journey to address any changes.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Franzoi et al, 1 "Implementing a PROACTive care pathway to empower and support survivors of breast cancer," researchers described implementation, survivors' and providers' experiences, satisfaction, and perceived usefulness of a proactive patient-centered survivorship care pathway consisting of four components: a personalized survivorship care plan (SCP), group support seminars and survivorship consultation at the end of treatment, access to a mobile application for management of symptoms, and decision aids for physicians to manage side effects and symptoms. Using the Reach, Effectiveness, Adoption, Implementation, and Maintenance framework to guide a process evaluation of this program, the researchers found that 75% of survivors received a SCP, 52% attended seminars and consultation, 60% assessed the mobile support application, and 96% who participated in the full pathway experience reported being satisfied.…”
mentioning
confidence: 97%